How does training methodology influence the tactical knowledge of football in stages of formation? - Fernandez, R. C.; Salguero, A.; Molinero, O.; Sanchez, J.; Yagüe, J. M. (MOJ Sports Medicine, 2018)
In recent decades, the teaching of sports in general and of football in particular, has evolved from a traditional technique-based approach, into something more flexible and adaptable to both the needs and characteristics of the player and above all, to the changing nature of the game itself. The aim of this research is to analyze the influence of an analytical methodology and other global tactical football knowledge. To do this we worked with a sample of 226 male football players belonging to grassroots football clubs, between the ages of 8 and 18. They were given the CECTAF to assess their tactical comprehension of football before and after completing a specific training program of each methodology, consisting of 12 training sessions over a 6 week period. Regarding the global tactical knowledge, we found significant differences in the variable "competitive category", highlighting the youth category with the highest values with 22, 69. Regarding variable "time of data collection" it is evident how values enhance after training processes, going from 21,45 in the first round intake, to values of 22,24 in the second one, in both methodologies, without there being significant differences. We can observe a similar trend in that global tactical knowledge, obtaining in analytical methodology values of 22,24, for global methodology 22,16 and 21,23 for the control group-with no significant differences being found here, the importance of the training process is again emphasized. Finally, there are positive correlations between the "competitive category" and global methodology with defensive individual tactic, offensive collective tactic and defensive collective tactic. This research stresses the importance of the training process as a base for integral/ fundamental improvement of the football player, adapted at all times to his/her developing process and to the methodological rigor that the forming process requires, regardless of the methodology used.